2022
DOI: 10.14202/vetworld.2022.1657-1664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary betaine on body temperature indices, performance, metabolism, and hematological variables of dairy heifer calves during hot summer conditions

Abstract: Background and Aim: Heat stress (HS) can negatively impact farm animal productivity and adversely affect animal welfare worldwide, placing a major financial burden on global livestock producers. Dietary betaine (trimethylglycine) has been known to have several biological functions, which may aid in offering beneficial effects on livestock productivity during HS conditions. However, information on the role of dietary betaine in heat-stressed dairy heifer calves is yet to be documented. Therefore, this study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…In addition, Xie et al (2015) reported that chronic heat stress can lead to tissue damage. Research has found that the cyclic heat stress pattern is more in line with the characteristics of summer temperature and closer to the actual living environment (Al Qaisi et al, 2022). Heat stress can affect intestinal microflora's activity and stimulate the hypothalamus's feeding center to reduce its excitability, leading to the decline of broiler growth performance and even death (Wang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Xie et al (2015) reported that chronic heat stress can lead to tissue damage. Research has found that the cyclic heat stress pattern is more in line with the characteristics of summer temperature and closer to the actual living environment (Al Qaisi et al, 2022). Heat stress can affect intestinal microflora's activity and stimulate the hypothalamus's feeding center to reduce its excitability, leading to the decline of broiler growth performance and even death (Wang, 2013).…”
Section: Introductionmentioning
confidence: 99%